(untitled) (Revista de Ciências Agroveterinárias, 2024)
Pseudothrombocytopenia is a false decrease in platelet count caused, most of the time, by pre-analytical errors, representing an important problem in canine and feline medicine. The objective was to evaluate the use of a vortex shaker for laboratory resolution of pseudothrombocytopenia in these species. The project was carried out with samples from canines (n=100) and felines (n=100) from the laboratory routine, which showed a decrease in platelet count in addition to the presence of platelet aggregates. Platelets were quantitatively evaluated pre- and post-treatment by automated bioimpedance counting and slide estimation. The treatment was carried out by vortex agitation at 3600 rotations per minute for three minutes. In parallel, the frequency of variations in platelet measurements of 100 canines and 100 felines was evaluated. There was a significant difference between pre- and post-treatment platelets (p<0,001 for canines and p=0,0097 for felines), obtaining higher values in all patients evaluated after treatment with agitation, with mean platelets within the reference values for the species evaluated. Felines had the highest frequency of pseudothrombocytopenia and platelet aggregates, but also the species that had the lowest dissociation of aggregates, considering that platelet dissociation was proportional to the intensity of pre-agitation aggregates in both species. It is concluded that the use of a shaker in the proposed protocol is capable of reducing the incidence of pseudothrombocytopenia, reducing the underestimated counts. However, the technique should not be used as the only parameter for resolving pseudothrombocytopenia, considering that the dissociation of aggregates through agitation is not complete, although it minimizes false diagnoses and helps the clinician in a more appropriate therapeutic approach.